Tannic acid elicits differential gene regulation in prostate cancer apoptosis - Kandir Sinan; Karakurt Sevtap; Gökçek-Saraç Çiğdem; Karakurt Serdar (Acta Pharmaceutica)
Prostate cancer is a significant global health concern that requires innovative therapeutic investigations. Here, the potential anticancer properties of tannic acid were evaluated by examining its effects on apoptosis in prostate cancer cell lines. PC-3 and LnCaP prostate adeno carcinoma cells, along with PNT1A prostate control cells, were cultured and divided into untreated and tannic acid-treated groups. Cell proliferation, cytotoxicity, and effects of tannic acid on the cell death mechanism were evaluated. mRNA expression levels of 84 genes were explored in cells following tannic acid treatment. Notably, tannic acid-induced down-regulation of several pro-survival genes, including ATM, BCL2, BCL2A1, BIK, BIRC2, BIRC3, BRE, CASP3, CASP6, CASP8, CHEK2, CRADD, PPIA, RPA3, TNFSF18, TRAF1, TRAF2, TRAF4, and TRAF5 in both cell lines. Moreover, tannic acid treatment led to the up-regulation of various pro-apoptotic genes, such as BCL10, BIRC3, BNIP3, CASP1, CASP5, CD40, CIDEB, DAPK2, FASLG, GADD45A, MYD88, RPA 3, TNFRSF10D, TNFRSF17, TNFRSF8, TNFSF13B, TNFSF4, TNFSF7, TNFSF8, TNFSF9, TP53, TRAF1, and TRAF2 in both PC-3 and LnCap cells. These findings highlight tannic acid’s ability to induce apoptosis in prostate cancer cells through pro-apoptotic pathways. This study concludes that tannic acid selectively inhibits prostate cancer cell growth.